Clinical outcomes of percutaneous coronary intervention for chronic total occlusion in prior coronary artery bypass grafting patients. Issue 1 (4th May 2021) - Shoaib, Ahmad; Mohamed, Mohamed; Curzen, Nick; Ludman, Peter; Zaman, Azfar; Rashid, Muhammad; Nolan, James; Azam, Ziyad A; Kinnaird, Tim; Mamas, Mamas A; ,
Abstract: Objective: To compare the clinical characteristics and outcomes in patients with stable angina who have undergone chronic total occlusion (CTO) percutaneous coronary intervention (PCI) in native arteries with or without prior coronary artery bypass grafting (CABG) surgery in a national cohort. Background: There are limited data on outcomes of patients presenting with stable angina undergoing CTO PCI with previous CABG. Methods: We identified 20, 081 patients with stable angina who underwent CTO PCI between 2007–2014 in the British Cardiovascular Intervention Society database. Clinical, demographical, procedural and outcome data were analyzed in two groups; group 1‐CTO PCI in native arteries without prior CABG ( n = 16, 848), group 2‐CTO PCI in native arteries with prior CABG ( n = 3, 233). Results: Patients in group 2 were older, had more comorbidities and higher prevalence of severe left ventricular systolic dysfunction. Following multivariable analysis, no significant difference in mortality was observed during index hospital admission (OR:1.33, CI 0.64–2.78, p = .44), at 30‐days (OR: 1.28, CI 0.79–2.06, p = .31) and 1 year (OR:1.02, CI 0.87–1.29, p = .87). Odds of in‐hospital major adverse cardiovascular events (MACE) (OR:1.01, CI 0.69–1.49, p = .95) and procedural complications (OR:1.02, CI 0.88–1.18, p = .81) were similar between two groups but procedural success rate was lower in group 2 (OR: 0.34, CI 0.31–0.39, p < .001). The adjusted risk of target vessel revascularization (TVR) remained similar between the two groups at 30‐days (OR:0.68, CI 0.40–1.16, P‐0.16) and at 1 year (OR:1.01, CI 0.83–1.22, P‐0.95). Conclusion: Patients with prior CABG presenting with stable angina and treated with CTO PCI in native arteries had more co‐morbid illnesses but once these differences were adjusted for, prior CABG did not independently confer additional risk of mortality, MACE or TVR.